P-shape monopole antenna design for WBAN application - Aabidi, E. S. (2013)
This paper presents P-shaped monopole antenna for WBAN application for 3.1 to 5.1GHz frequency band. The design and simulation of proposed antenna for WBAN applications in the free space and close proximity of body surface has been done using CST Microwave Studio. The proposed antenna was designed on the FR4 substrate with dielectric constant, εr of 4.4 and thickness of 1.6mm. The ﬁnal optimized design is 32×28mm2. The antenna is suitable to be deployed for WBAN application.